KINERJA BIDANG REHABILITASI SOSIAL DALAM PERLINDUNGAN ANAK (STUDI KASUS EKSPLOITASI ANAK DI KOTA PEKANBARU) - Erdiantikah, Helmida; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The case of exploitation of children both economically and sexually is one of the problems in the country that has never been resolved. There are no exception cities in Riau especially in Pekanbaru City which often get the spotlight from the Regional Government. The Social Rehabilitation Section in Child Protection as the party responsible for realizing social welfare in the area of Pekanbaru City has done various ways to be able to provide protection to minors, but children who are economically and sexually exploited are still mushrooming in this Sorcerer City . The purpose of this study was to determine the Performance of the Social Rehabilitation Section in Child Protection and analyze the inhibiting factors of the Social Rehabilitation Section in Child Protection. The theoretical concept used is the theory of Organizational Performance by Agus Dwiyanto in Aprilia (2018: 40), namely: Productivity, Service Quality, Responsiveness, Responsibility and Accountability. This study uses a qualitative method of case study approach, the selection of informants using Purposive Sampling techniques with data collection techniques include: observation, interviews and documentation. The results of this study can be seen that the Performance of the Social Rehabilitation Section in the Protection of Children in the City of Pekanbaru has been optimal, as seen from the cases resolved each year always increasing. However, there are some obstacles experienced by the Social Rehabilitation Section in Child Protection, namely Budget, Communication, and inadequate facilities and infrastructure.                                                                                                            Keyword: Performance, Organizational and Organizational Performance